The Effect of Grapex on Wounds Healing in Patients with Scleroderma: A Randomized Controlled Clinical Trial - Hemmati, Ali Asghar; Deris Zayeri, Zeinab; Rajaei, Elham; Ghanavati, Maryam (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Scleroderma (SC) is a connective tissue disease, characterized by diffuse microangiopathy and excessive production of collagen. The current study aimed to investigate the effectiveness of Grapex extract in improving the wound of patients with scleroderma. Methods: This randomized controlled double-blind clinical trial was performed from 2018 to 2019 on patients with scleroderma referred to Golestan Hospital in Ahvaz, Iran. Forty patients with active SC were selected and randomly divided into two groups. Patients applied the ointment twice a day for 4 weeks on the surface of their wounds. After four weeks of using the cream, the rate of wound healing was determined by clinical examination of the wounds. Results: 6 people were excluded from the study due to the lack of referral and final analyzes were performed on 34 patients (16 patients in the control group and 18 patients in the case group). The results of this study showed that there was a significant difference between the two groups in terms of response to treatment (p <0.0001). At the end of the fourth week, 88.89% of the patients in the case group (16 of the 18 patients) achieved complete healing of the wounds in comparison with 18.75% of the control group (3 of the 16 patients). Neither the control group nor the case group had a significant association between response to treatment with age and gender of patients, type of scleroderma, duration of illness, and symptoms. Conclusion: This study showed the effectiveness of Grapex cream ointment in healing scleroderma wounds. Therefore, Grapex cream is an effective, inexpensive, safe, and available medicine that can be used to accelerate wound healing in patients with scleroderma. *Corresponding Authors: Elham Rajaei, Email: elhamrj@gmail.com Please cite this article as: Hemmati AA, Deris Zayeri Z, Rajaei E, Ghanavati M. The Effect of Grapex on Wounds Healing in Patients with Scleroderma: A Randomized Controlled Clinical Trial. Arch Med Lab Sci. 2021;7:1-10 (e1). https://doi.org/10.22037/amls.v7.31059